2013
DOI: 10.1111/ijs.12007
|View full text |Cite
|
Sign up to set email alerts
|

Worse Stroke Outcome in Atrial Fibrillation is Explained by More Severe Hypoperfusion, Infarct Growth, and Hemorrhagic Transformation

Abstract: Background Atrial Fibrillation (AF) is associated with greater baseline neurological impairment and worse outcomes following ischemic stroke. Previous studies suggest that greater volumes of more severe baseline hypoperfusion in patients with history of AF may explain this association. We further investigated this association by comparing patients with and without AF on initial examination following stroke using pooled multimodal magnetic resonance imaging (MRI) and clinical data from the Echoplanar Imaging Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(117 citation statements)
references
References 37 publications
6
105
1
5
Order By: Relevance
“…4,8 Large registries and trials have shown that AF-related strokes constitute the most severe ischemic stroke subtype. 3,5,6,9 Yet, the majority of studies compared patients with AF-related strokes to patients with strokes deemed unrelated to cardioembolic sources; i.e., those with small or large vessel disease related strokes. 5,6,9 An important remaining question is whether the risk for a unfavorable post stroke outcome after CES differs based on the underlying pathomechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,8 Large registries and trials have shown that AF-related strokes constitute the most severe ischemic stroke subtype. 3,5,6,9 Yet, the majority of studies compared patients with AF-related strokes to patients with strokes deemed unrelated to cardioembolic sources; i.e., those with small or large vessel disease related strokes. 5,6,9 An important remaining question is whether the risk for a unfavorable post stroke outcome after CES differs based on the underlying pathomechanism.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6,9 Yet, the majority of studies compared patients with AF-related strokes to patients with strokes deemed unrelated to cardioembolic sources; i.e., those with small or large vessel disease related strokes. 5,6,9 An important remaining question is whether the risk for a unfavorable post stroke outcome after CES differs based on the underlying pathomechanism. Specifically, do patients with AF-related CES have a greater ischemic stroke severity and worse outcomes than patients with non-AF related CES?…”
Section: Introductionmentioning
confidence: 99%
“…Presence of atrial fibrillation in stroke patients most likely via poorer collateral blood supply is associated with more severe hypoperfusion and hence with increased infarct growth and volume, more frequent and more severe HT and worse stroke outcome [96].…”
Section: Atrial Fibrillationmentioning
confidence: 99%
“…58 The risk of hemorrhagic transformation is also increased by pre-existing patient factors such hyperglycemia, 59 poor collateral flow, 60 anticoagulant therapy, and atrial fibrillation/cardioembolic stroke. 61,62 Certain imaging parameters may also signal an increased risk of hemorrhagic transformation following thrombolytic therapy. With regard to treated anterior circulation infarcts within 6 hours, a retrospective study by the MR Stroke Study Group Investigators found a 5.8-fold increased risk of symptomatic Intracerebral hemorrhage (ICH) with large (>100 mL) compared with small (<10 mL) pretreatment DWI volume infarct cores, and a 2.8-fold increased risk compared with moderate (10 to 100 mL) core volumes.…”
Section: Complications Of Acute Infarction and Reperfusion Therapymentioning
confidence: 99%